BIAYA PENANAMAN DI TAHURA SULTAN ADAM MANDIANGIN, KALIMANTAN SELATAN - Maimunah Maimunah; Daniel Itta; Maghdalena Yoesran (Jurnal Sylva Scienteae, 2020)
The aim of this research is to calculate the cost of planting activities in the Sultan Adam Forest Park, Mandiangin area. The benefits of this research are expected to be able to provide information and an overview of rehabilitation costs, so it can be considered for relevant agencies to be able to reduce rehabilitation costs, especially in the Sultan Adam Forest Park, Mandiangin area. The research method used was descriptive analysis method by summing all the cost components of planting activities in Sultan Adam Mandiangin Forest Park, South Kalimantan. The total costs obtained will be distributed based on the area of the research, so it would get the cost of every hectare for planting activities in 2013, 2014 and 2015. The results of this research indicate that the cost of planting per hectare in 2013 was IDR 11,188,750 / hectare in 2014 was IDR 12,363,100 / hectare and in 2015 it reached IDR 13,876.00 / hectare.